Heart failure disease management program: A review. Issue 31 (5th August 2022) - AlHabeeb, Waleed
Abstract : Disease management programs (DMPs) have shown great potential for optimizing care of chronically ill patients, thereby improving health outcomes and patient satisfaction. This had led to an overall reduction in healthcare costs. Longer life expectancy has led to increased utilization of healthcare facilities, which may lead to a rise in costs. DMPs are an effective means of improving care and compliance and ultimately curbing inappropriate resource utilization. The present study reviews different definitions proposed for disease management, its components, the evidence behind it, and the conditions for success. It also examines heart failure management as an example of a DMP, exploring the complexity surrounding implementation of guideline-based approaches in patient care. A literature search on DMPs was conducted using PubMed, MEDLINE, and Google Scholar, including heart failure management programs from articles published from 2000 to 2020. This reviewed emphasized on the management of important biomarkers and cardiovascular indicators such as glycemic levels, urine output to improve efficacy of disease management programme during patient treatment. The review concluded that diseases like heart failure can be combat by improving the quality of care for patients and reducing the burden on the public healthcare system. Moreover, DMPs have proved to be an effective way of improving care and compliance with treatment.